Identification of Science Learning Difficulties During the Covid-19 Pandemic in Class V SDN Peterongan - Hanum, Arfanny (Universitas Sebelas Maret, 2020)
This study aims to identify problems in learning science at home during the Covid-19 pandemic that occurred in fifth grade students at SDN Peterongan in the 2019/2020 school year. The method used in this research is descriptive qualitative with a phenomenological approach. The data sources of this study were all fifth grade students, parents, and fifth grade teachers. The data collection technique was done by using questionnaires, interviews, and documentation studies. The data validity test used in this study was technical triangulation and source triangulation. Data were analyzed using the data analysis model Miles and Huberman. The results of this study indicate that student learning problems occur due to lack of interest and motivation of students and students have difficulty understanding concepts. Only 36% of students showed interest in online science learning, and 70% of students had difficulty understanding concepts. The problems that occur are caused by several factors. Based on these factors, efforts that can be made to solve learning problems experienced by students are to increase students' interest and motivation by choosing learning methods and media that make students interested and become more active, provide enrichment and remedial, and maintain communication with parents to monitor student learning difficulties at home.